Lax pair for strings in Lunin-Maldacena background. - FROLOV, SERGEY (My University, 2005)
Recently Lunin andMaldacena used an SL(3,R) transformation of the AdS5?S5 background to generate a supergravity solution dual to a so-called -deformation of N = 4 super Yang-Mills theory. We use a T-duality-shift-T-duality (TsT) transformation to obtain the -deformed background for real ? , and show that solutions of string theory equations of motion in this background are in one-to-one correspondence with those in AdS5 ?S5 with twisted boundary conditions imposed on the U(1) isometry fields. We then apply the TsT transformation to derive a local and periodic Lax pair for the bosonic part of string theory in the -deformed background. We also perform a chain of three consecutive TsT transformations to generate a three-parameter deformation of AdS5 ? S5. The three-parameter background is dual to a nonsupersymmetric marginal deformation of N = 4 SYM. Finally, we combine the TsT transformations with SL(2,R) ones to obtain a 6 + 2 parameter deformation of AdS5 ? S5.
PUBLISHED
Keywords: Mathematics; string theory; super Yang-Mills theory